Analisis tren rasio net imbalan dan net operation margin pada perbankan syariah - Afifa, Fania Eka Bella; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This study analyzes the trend of Net Income (NI) and Net Operating Margin (NOM) ratios at PT Bank Mega Syariah Tbk during the period 2018-2023 to evaluate its financial performance and operational efficiency. The results showed that the Net Reward (NI) ratio was generally in the healthy category, although it had dropped to the moderately healthy category in 2020 and 2021. However, in 2022-2023, NI showed improvement again, reflecting the recovery of sharia-based income performance. Meanwhile, the Net Operating Margin (NOM) ratio shows more significant fluctuations. From 2018 to 2020, NOM was in the unhealthy category, but managed to reach the healthy category in 2021 and 2022. However, in 2023, the NOM ratio declined back to the unhealthy category. This finding shows that although PT Bank Mega Syariah Tbk is able to improve its income performance, its operational efficiency still requires improvement in order to maintain stability and consistently healthy category. This research provides important insights for bank management in designing strategies to improve financial performance in the future